Marketing of Handicrafts - A Case Study of Brass Items Manufacturing Units in Srikakulam District of Andhra Pradesh - Kama Raju, T.; Santosh Ranganath, N. (Indian Journal of Marketing, 2010)
Handicrafts constitute an important segment of the decentralized sector, which provides employment to nearly three million artisans scattered all over the country. Hardly, there is a village or a city of any importance without artisans and craftsmen. The Industry is both rural and urban. It transcends sectarian, linguistic and communal barriers. Thus, the problems of the Handicrafts Industry are that of the premier home industry, national in its significance, cosmopolitan in its range and heterogeneous in its character. Marketing is a vital function for every commercial organization. In fact, marketing forms the basis to establish and operate the activities in the right direction. The end objective of any commercial organization is to ensure maximum sales of its products at reasonable profit. The large scale industries which have abundant financial and other resources may be able to establish an efficient marketing organization of their own, but to the small scale and cottage industries, it is not possible to have such an organization due to resource limitations. Handicraft units, which are mostly run by individuals with sole-proprietary type of organization, cannot afford to have a separate and well-organized marketing system. The artisan-cum-proprietor of the unit devotes his entire time on production. He possesses very little knowledge and information relating to marketing of his products. Unfortunately, the artisans of handicrafts industry never give much importance to the marketing function. Hence, the artisans mostly depend upon the Master craftsmen, Lepakshi Emporium and private outlets for disposal of their finished products. The Brass artisans are one of the most traditional handicraft makers of the Srikakulam District, which are catering to need of the people of Srikakulam District and its neighbouring districts and to some other states by supplying brass utensils. Against this background, the researcher has chosen this topic with the following objectives.